Application of Discussion Methods and Memory Board Games to Increase Student Activity and Learning Outcomes in History Learning - Esti Normalita; Charlotta Svonni; Paul Maluleka (Indonesian Journal of Education Research (IJoER), 2023)
Purpose of the study: The aim of this research is to apply discussion methods and memory board games to increase student activity and learning outcomes in history learning. Methodology: This type of research is classroom action research. The samples in this research were class X history students and teachers in high school. The sampling technique uses purposive sampling. Data collection techniques through observation, interviews and tests. This research uses qualitative analysis and quantitative analysis. Main Findings: The results of the research can be concluded that the application of discussion methods and memory board games can increase the activity and learning outcomes of class X students in high school in learning history. Before the action was taken, the average activity level for class X was 36.16%. In cycle I the average percentage of student activity indicators was 79.46%, increasing in cycle II by 9.38% to 88.84%. The class average score in cycle I, namely the pretest, was 48.18 and increased in the posttest by 26.32 to 74.5. The average class score in cycle II, namely the pretest, was 46.82 and increased in the posttest by 33.72 to 80.54. Novelty/Originality of this study: As a novelty from previous research, this research will investigate the benefits of combining the use of discussion methods and memory board games in history learning. Then, through this research, the impact of memory board games on students in learning history will be known.